2
$\begingroup$

Let $M$ be a $n\times n$ definite positive real diagonalizable matrix and $D$ the diagonal matrix of eigenvalues of $M$ (all positive, then). Let $P$ be a matrix the columns of which form a basis of eigenvectors. Then we have $M=PDP^{-1}$.

As $P$ is not unique, let $Q$ be another matrix the columns of which form an another basis of eigenvectors. Then we have $M=QDQ^{-1}$.

Now suppose I have to deal with two matrices which are: $A=PD^{1/2}P^{-1}$ and $B=QD^{1/2}Q^{-1}$...

Can I conclude that $A=B$ ? It's my first intuition, but I couldn't manage to go through any demonstration or any counter-example. Could you provide me some help?

$\endgroup$
  • 1
    $\begingroup$ I think the answer depends on your definition of $D^{1/2}$. Is it just any matrix $X$ such that $X^2 = D$? Or do you choose the roots in a specific way? $\endgroup$ – Claudius Jul 20 at 8:08
  • $\begingroup$ OK, sorry! I forgot to say that $M$ is positive definite, so that eigenvalues are positive. Then $D^{1/2}$ is the diagonal matrix containing the square roots of the eigenvalues... $\endgroup$ – Andrew Jul 20 at 8:14
  • $\begingroup$ Just to make it clear: with square roots you mean positive square roots, right? $\endgroup$ – Claudius Jul 20 at 8:16
  • $\begingroup$ I amended the post... To answer your questiuon : yes. If $D$ contains $\lambda$, then $D^{1/2}$ contains $\sqrt{\lambda}$ $\endgroup$ – Andrew Jul 20 at 8:19
3
$\begingroup$

The answer is yes. If $\lambda$ und $\mu$ are two (positive) eigenvalues, then we have $\lambda =\mu \iff \sqrt\lambda = \sqrt\mu$ (since we take positive roots, right?). This implies that for $X\in {\rm GL}_n(\Bbb R)$ we have the equivalences $$ \begin{align*} XDX^{-1} = D &\iff D^{-1}XD = X\\ &\iff (D^{1/2})^{-1} XD^{1/2} = X\\ &\iff XD^{1/2}X^{-1} = D^{1/2}. \end{align*} $$ More precisely, if $D$ has the form ${\rm diag}(\lambda_1I_{n_1},\dotsc, \lambda_r I_{n_r})$ (with $I_{n_j}$ the $n_j\times n_j$-identity matrix and $\lambda_i\neq \lambda_j$ for $i\neq j$) then $$ \{X\in {\rm GL}_n(\Bbb R) \mid D^{-1}XD = X\} = {\rm diag}({\rm GL}_{n_1}(\Bbb R),\dotsc, {\rm GL}_{n_r}(\Bbb R)). $$ (And the same for $D$ replaced by $D^{1/2}$.)

Now take $P,Q \in {\rm GL}_n(\Bbb R)$ with $PDP^{-1} = QDQ^{-1}$. Then $(Q^{-1}P) D (Q^{-1}P)^{-1} = D$, so by the above also $(Q^{-1}P) D^{1/2} (Q^{-1}P)^{-1} = D^{1/2}$. Therefore, $PD^{1/2}P^{-1} = QD^{1/2}Q^{-1}$.

$\endgroup$
  • $\begingroup$ Sorry, I must be tired... Could you explain more clearly how you go from the first equivalence to the second and then to the third? $\endgroup$ – Andrew Jul 20 at 8:50
  • $\begingroup$ The first and third equivalence is just a rearrangement of matrices. The second one should be clarified in the immediately following part. If you don't understand something, please ask a precise question. $\endgroup$ – Claudius Jul 20 at 8:52
  • $\begingroup$ Claudius, the precise question is: I don't understand why $D^{-1}XD = X \iff (D^{1/2})^{-1} XD^{1/2} = X$ $\endgroup$ – Andrew Jul 20 at 9:02
  • $\begingroup$ I already explained this in my answer. I simply don't know what your problem is. And you seem not willing to elaborate on your problem. $\endgroup$ – Claudius Jul 20 at 9:05
  • $\begingroup$ OK, Claudius, if you don't want to explain more clearly why $D^{-1}XD = X \iff (D^{1/2})^{-1} XD^{1/2} = X$, then let's go. It does not give me any useful explanation and you do not want to understand that I do not understand some of your statements. $\endgroup$ – Andrew Jul 20 at 9:10
3
$\begingroup$

Yes. Suppose $\lambda_1,\ldots,\lambda_k$ are the distinct eigenvalues of $M$ (so that $1\le k\le n$). Let $f$ be any polynomial such that $f(\lambda_i)=\lambda_i^{1/2}$ (e.g. take $f$ as a Lagrange interpolation polynomial). Then $f(D)=D^{1/2}$. It follows that $$ A=PD^{1/2}P^{-1}=Pf(D)P^{-1}=f(PDP^{-1})=f(M) $$ and similarly $B=f(M)$ too.

$\endgroup$
  • $\begingroup$ Thanks. For the moment, I dont know enough about Lagrange interpolation polynoms to understand why $Pf(D)P^{-1}=f(PDP^{-1})$, but I will investigate this; it sounds interesting. $\endgroup$ – Andrew Jul 20 at 14:12
  • $\begingroup$ @Andrew This is not specific to Lagrange interpolation polynomial. The equality $Pf(D)P^{-1}=f(PDP^{-1})$ holds for any polynomial $f$. $\endgroup$ – user1551 Jul 20 at 15:00
  • $\begingroup$ Good, thanks. So Lagrange is just for assuming that $f$ is not any polynomial but a polynomial for which $f(\lambda_i)$ has value ${\lambda_i}^{1/2}$... $\endgroup$ – Andrew Jul 20 at 15:13
  • $\begingroup$ @Andrew Yes, its sole purpose is to ensure that $f(D)=D^{1/2}$. $\endgroup$ – user1551 Jul 20 at 15:17
0
$\begingroup$

Yes, you can conclude that $A=B$. To see this in a straightforward manner, using $P^{-1}P=I$, note that $$M^2 = PDP^{-1}PDP^{-1} =P D^2 P^{-1}.$$ In the same manner, it follows that $$M^{\frac{1}{2}} = P D^{\frac{1}{2}}P^{-1} = Q D^{\frac{1}{2}} Q^{-1},$$ which gives $A=B$.

$\endgroup$
  • $\begingroup$ Maybe it would be helpful to close the loop with: $$M = M^{\frac{1}{2}} M^{\frac{1}{2}} = PD^{\frac{1}{2}}P^{-1} P D^{\frac{1}{2}} P^{-1} = P D P^{-1}$$. $\endgroup$ – ChainedSymmetry Jul 20 at 14:03
  • $\begingroup$ Looks nice. But although $D^{1/2}$ is clear, $M^{1/2}$ is not (for me...). How can we say that $(PDP^{-1})^{1/2}=PD^{1/2}P^{-1}$? I mean, $(PDP^{-1})^{1/2}$ is a matrix $X$ defined by $X^2=(PDP^{-1})^{1/2}$. Although $PD^{1/2}P^{-1}$ works well, it may not be the unique matrix that works well. $\endgroup$ – Andrew Jul 20 at 14:06
  • $\begingroup$ sorry, i wanted to write: $X^2=PDP^{-1}$ $\endgroup$ – Andrew Jul 20 at 14:14
  • $\begingroup$ The key assumption is that we are taking the same square root of D for both A and B, (i.e. $(D^{\frac{1}{2}})_A = (D^{\frac{1}{2}})_B$. With that assumption, then there is no ambiguity in the equality $A=B$.Taking the root M impacts the magnitude (eigenvalues) of M leaving the direction (eigenspace) of M untouched (up to sign choice for each eigenvalue handled in the assumption above). You might find link helpful reading. $\endgroup$ – ChainedSymmetry Jul 20 at 14:49
  • $\begingroup$ Hum, could you please explicit the steps between $(PDP^{-1})^{1/2}$ and $PD^{1/2}P^{-1}$? You said "in the same manner...", but I still don't understand that manner. Thank you. $\endgroup$ – Andrew Jul 21 at 5:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.